Impact of NOM on flocs created in the drinking water process - Cairns, Peter Ryland (Cranfield University, 2008)
Increased regulatory pressure to meet THM standards with the possible introduction of HAA regulations means that organic matter, the predominant DBP precursor needs to be removed effectively from site whilst coping with increased economic and environmental drivers for change. Organics are typically removed via coagulation / flocculation which can be optimised by operating in the correct zeta potential range (-10mV and +8mV) and the correct DOC:FE coagulant dose ratio (1:1). However, due to spatial and temporal changes in bulk NOM and its fractional character there are no standard operating conditions, consequently sites have to respond to changing conditions. Seasonal trends in DOC and THMFP levels were measured under optimised and current operational conditions. Results indicated that UV254 could be used to predict coagulant dose and zeta potential could be used to indicate optimum coagulation conditions for DBP precursor removal across 16 sites. Under optimised condition improved organics removal and floc properties was observed across all source waters however the degree to which this occurred depended on the source water. Understanding of the fractional make up is thus important to assess the potential for optimisation of the coagulation process. Providing the electrostatic forces are minimised, increasing the NOM content of the floc matrix will lead to an increase in floc strength. One of the implication of optimised coagulation conditions were that flocs could be created at lower retention time then quoted by best practice guidelines. As such a 66% decrease in flocculation energy could be achieved without any detrimental impact to floc quality or removal efficiency. One of the important findings is that due to the inherent difference in source waters, optimisation for a site can vary in terms of cost and clarified water quality, hence each site needs to be evaluated before schemes are carried out.
Keywords: coagulation; flocculation; NOM content; source waters; organics removal; NOM content